Vision loss following snakebite in a patient with controlled aplastic anemia - Kweon,EY (2009)
Viper venoms act mainly on blood and blood vessels. Reports of ophthalmic manifestations after snakebite include ptosis and ophthalmoplegia. In the current study, we describe a case that developed bilateral retinal and subretinal hemorrhage following snakebite. Bilateral retinal hemorrhage is a rare ocular complication of snake envenomation and has not been reported with fundus photographs in the literature so far.